Франчайзинг - Гаряєва, Ганна Михайлівна; Хільченко, А. М.; Поліщук, О. Я. (НТУ "ХПІ", 2014)
В статті здійснюється аналіз державного регулювання франчайзингових відносин, розглядаються невідповідності між правовим регулюванням франчайзингу та фактичною стадією розвитку комерційних відносин, проблеми реєстраціЇ договорів франчайзингу у Цивільному та Торговельному Кодексі України, законодавстві щодо захисту прав інтелектуальної власності, економічної конкуренції та прав споживачів та інших нормативних документах та пропоновані заходи щодо їх вирішення.

The article analyzes the state regulation of franchise relations, is considered discrepancy between the legal regulation of franchising and the actual stage of commercial relations, problems of registration of franchising agreements in Civil and Commercial Code of Ukraine, Legislation on the protection of intellectual property rights, economic competition and consumer rights and other legal documents and other regulations. Are proposed measures to solve these issues (problems) that aquire special importance (weight) in a new round of global economic crisis in 2014, which encourages the development of franchise systems and their active involvement and increase of funding in the public sector of the economy as the main tools to attract foreign investment in the development of the national economy, which includes a variety of market segments.
Franchise
Keywords: франшиза; франчайзинг угоди; кодекс; franchisor; franchise; franchise agreements; codes